The Society of Jesus in Ireland, Scotland, and England, 1598-1606: Lest Our Lamp Be Entirely Extinguished - McCoog, S.J. Thomas M. (Catholic Christendom, 1300-1700 Ser, 2017)
Contents -- Preface -- Abbreviations -- Introduction -- A Jesuit Reading of Elizabethan Catholic History -- A Critique of Holt -- Conflict and Collusion -- Historiographical Correctives -- History of Elizabethan Jesuits -- An Extinguished Lamp? -- The Succession -- Jesuit-Secular Conflict -- Intra-Jesuit Tension -- Conclusion -- Chapter 1 -- "Apostata Jesuits, Apostata Secular Priests": Ongoing Domestic Discontent, 1598-1600 -- Introduction -- Concerted Attack on English Jesuits -- Fisher's Memorial -- Hope Rooted in Rumours: Jesuits in Scotland -- Relaunching the Jesuit Mission to Ireland -- Ecclesiastical Novelties: Prefecture and Archpresbyterate -- Questioning the New English Order: The Beginning of the Appellant Controversy -- Superior of the Mission -- "May God give victory to him whose cause is just": Jesuits in Ireland -- A Brief Peace among English Catholics -- Shepherding His Jesuit Flock -- The Essex Rebellion -- Conclusion -- Chapter 2 -- Peace Unattained: 1598-1600 -- Introduction -- Peace Overtures within the Catholic Community -- Adjustments to the New Ecclesiastical Order -- The Continuing Debate over the Succession -- Re-Organization of the Scottish Mission -- The Intercession of the Nuncio -- The Appeal to Rome -- Troubles at the English Colleges -- The Continuing Struggle in the Low Countries -- James Makes His Move -- O'Neill's Crusade -- Conclusion -- Chapter 3 -- "Havinge holines in there mouthes but wickednes in there heartes": English Jesuits on the Defensive, 1601-1602 -- Introduction -- Fallout from the Essex Rebellion -- The Second Appeal -- Taking the Queen: Catholicism in Scotland -- The Arrival of the Spanish in Ireland -- Potent Passions Propel the Appellant Dispute -- Conflict More Bitter -- "Heresy triumphant": Conditions in Scotland -- Post-Kinsale Ireland -- Denouement? -- Conclusion -- Chapter 4